The affective infrastructure of a protest camp: Asylum seekers’ ‘Right to Live’ movement - Näre, Lena; Jokela, Maija (The Sociological review (Keele), 2023)
In this article, we develop the concept of affective infrastructure as the entanglement of affects, meanings and materiality to analyse protest camps as a specific organisational form of social and political movement. Drawing on two ethnographic research projects investigating an asylum seekers’ protest camp in Helsinki, Finland, we argue that affects can be understood as having an infrastructural quality. The article contributes to research on affective politics by empirically studying the affective infrastructure of a protest camp. We distinguish between three interrelated dimensions of the affective infrastructure of a protest camp. First, affects are mobilised to mediate place-related meanings, the alteration of which is crucial to all protest camps. Second, affects are involved in creating the social space and atmosphere necessary to sustain a long-lasting protest. Third, affects impress themselves on abstract objects and ideas that must be managed as a part of the protest’s political message. Affects not only join subjects and objects together but also divide them, illustrating that an infrastructure becomes visible when it staggers or fails.